Bioactive Components, Diet and Medical Treatment in Cancer Prevention (Springer International Publishing, 2018)
The high rate of urbanization and a steady increase in per capita income has improved the socio-economic status of people all over the world. This has resulted in drastic changes in their lifestyle and food consumption patterns, where traditional foods are being replaced with more ready-made junk foods with few servings of fresh vegetables and fruits. It has been postulated that industrialization has caused change in food choice, dietary pattern modification and resulted in a sedentary lifestyle. In addition, contaminated foods with unsafe microbes and chemical hazards are increasing. All of these events have resulted in an increased risk of cancer, the leading cause of mortality and morbidity worldwide. This book will provide a basic understanding of cancer, its risk factors, preventive measures, and possible treatments currently available, as well as identifying the different dietary factors that might synergize with a sedentary lifestyle in the etiology of cancer, and its prevention measure.